Fitness Of The Green Open Space In The Road Based On The Regulation Applying In The Barabai Urban - Andi R. Aulia Ramadanti; Bayu P. Putera; Fahmi Arif; Maulidah Maulidah (ESE International Journal (Environmental Science and Engineering), 2018)
The road network matching is very important in the comfort of pedestrian users, with guidelines or regulations that apply to the selection of trees on the road network system as a reference in choosing a park that is suitable for road boundaries. Barabai city which has a lot of mahogany trees on the side of the road, it can be said that Barabai Urban has followed the applicable regulations and the benefits for the tree also provide O2 oxygen which makes the surrounding air fresh so that the air reduces problems with air pollution. large trees are quite dangerous for pedestrians when strong winds and roots that cause damage to road borders with that need a good snack so that these problems are resolved for Barabai Urban.